Pengaruh Stres Kerja dan Kepuasan Kerja Terhadap Turnover Intention Perawat Rumah Sakit Prima Pekanbaru - Deswarta, Deswarta; Masnur; Adil Mardiansah (LPPM Universitas Sains dan Teknologi Komputer, 2021)
This study aims to determine how much influence Job Stress and Job Satisfaction have on Turn Over Intention of Nurses at Prima Pekanbaru Hospital, namely by Testing and Analyzing the Significant Effect of Job Stress and Job Satisfaction on Turn Over Intention Simultaneously, then Testing and Analyzing the Significant Effect Between Job Stress and Job Satisfaction on Turnover Intention Partially. The population in this study were 206 primary hospital nurses. however, as the sample in this study, there were 67 nurses using the slovin formula. The method used is by using purposive sampling method. The research data were analyzed by multiple linear regression analysis and processed using the SPSS for windows version 20 application. The results of the study showed that job stress and job satisfaction had an effect on the turn over intention of nurses at the Pekanbaru Prima Hospital.